Correlated Factors with Health Status among Residents in Urban and Rural Areas in Indonesia - Xaviera, Virnimuthia; Ainy, Asmaripa (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
The increase in health status is not only the government’s responsibility but also the self-awareness of each individual. Accelerating health information will affect one’s health status; digital access can significantly affect health status. This research analyzes the correlation between age, gender, family size, marital status, educational level, and digital access to health status in urban-rural residents in Indonesia. This research type is quantitative with a cross-sectional model. This research is using secondary data. The data is collected from the seventh wave of the World Value Survey from 2017 to 2022. The population of this region is 2,912 Indonesian citizens, with 789 urban citizens and 2,123 rural citizens in Indonesia as samples. The results of the analysis show a significant correlation between digital access and public health status among Indonesia’s urban citizens. It is discovered by a statistical result with a p-value <0,05, which is < 0,002 [OR 95% Cl = 2,5]. It is also proven by the results of the analysis of Indonesia’s rural citizens that there is a significant correlation between digital access and health status. It is discovered by a statistical result with a p-value <0.05, which is 0.000 [OR 95% Cl = 2,1]. The population in rural and urban areas utilizing digital access to maintain good health status is predominantly composed of female respondents in their productive age (15–64), with family members ≤4, engaged in employment, married, and having a high level of education.  Keywords: Digital access, health status, rural, urban